STRATEGI PENINGKATAN MOTIVASI KERJA MELALUI PELATIHAN KEPEMIMPINAN BAGI APARATUR PEMERINTAH LOKAL DI DISTRIK WALELAGAMA KABUPATEN JAYAWIJAYA PROVINSI PAPUA PEGUNUNGAN - Tukijan, Tukijan; Ayu Anggraini Tambunan; Bambang Supeno Domi; Angela Jelila Yare (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2024)
This study aims to explore the impact of leadership training on work motivation among village apparatus in Walelagama District, Jayawijaya Regency. Given the geographical challenges and limited resources, low work motivation hinders the performance of local government. Leadership training, designed contextually by integrating local values such as mutual cooperation, is expected to enhance work motivation and public service quality. This qualitative research uses a case study approach involving Focus Group Discussions (FGD) and interviews with village apparatus. The results show that leadership training based on local culture is effective in improving work motivation, strengthening team coordination, and enhancing public service quality. Although challenges in implementation exist, this training significantly contributes to improving the capacity of local government apparatus and governance quality in Walelagama District